Prevalence of Microalbuminuria in Adult Patients with Sickle Cell Disease in Eastern Saudi Arabia - Ahmed M. Alkhunaizi; Adil A. Al-Khatti; Mansour A. Alkhunaizi (International Journal of Nephrology)
Background. Proteinuria is a common feature of sickle cell nephropathy (SCN) that can progress to renal insufficiency and end stage renal disease. Microalbuminuria (MA) is the earliest manifestation of SCN and precedes the development of overt proteinuria. In addition to the renal consequences, MA is linked to cardiovascular complications. Periodic screening and early detection of MA allow early intervention that may reduce the risk of progression to advanced renal failure and cardiovascular diseases. Objective. The aim of this study was to investigate the prevalence of MA in patients with SCD in the eastern region of Saudi Arabia. Methods. A prospective cross-sectional observational study was conducted at Johns Hopkins Aramco Healthcare (JHAH). Urine samples of SCD patients 18 years old and older were tested for the presence of MA using urinary albumin over creatinine ratio (ACR). Correlation was tested with multiple variables including age, gender, body mass index (BMI), hemoglobin level, blood pressure, blood transfusion history, pain episodes, and use of hydroxyurea. Results. Urine samples were tested on 72 patients. The mean age of the study cohort was 35±16.9 years. Microalbuminuria was detected in 18 patients (25%). No correlation was found with any of the tested variables. Conclusion. Microalbuminuria is a common finding in patients with SCD in eastern Saudi Arabia. Patients with SCD should be screened for MA, and those with positive tests should probably be treated with antiproteinuric agents that may slow the progression to advanced stages of renal failure and decrease the risk of cardiovascular diseases.